OP0113 HISTOLOGICAL AND MOLECULAR PORTRAIT OF THE SYNOVIAL TISSUE IN EARLY TREATMENT-NAÏVE PSORIATIC ARTHRITIS IN COMPARISON WITH RHEUMATOID ARTHRITIS. (June 2019) - Nerviani, Alessandra; Ribera, Gloria Lliso; Boutet, Marie Astrid; Goldmann, Katriona; Kelly, Stephen; Bombardieri, Michele; Lewis, Myles; Humby, Frances; Pitzalis, Costantino
Abstract : Background: Psoriatic Arthritis (PsA) and Rheumatoid Arthritis (RA) are autoimmune joint diseases characterised by chronic inflammation of the synovial tissue (ST). It has been previously suggested that PsA-ST has less marked hyperplasia of the synovial lining and fewer infiltrating T/B cells in comparison with RA. However, several confounders such as treatment, disease duration, sampling techniques and predominance of large joints samples may have influenced these findings. Objectives: To compare the synovial features of PsA/RA at the beginning of the disease process and prior to any treatment for defining their histological/molecular individual characteristics, and to correlate the histological pattern with clinical parameters. Methods: 183 consecutive treatment-naïve patients with <12 months symptoms and active synovitis of at least one joint were enrolled into the Pathobiology of Early Arthritis Cohort (PEAC) at the Barts Health NHS Trust, and underwent a baseline US-guided synovial biopsy of an inflamed joint. ST inflammatory infiltrate was evaluated by semi-quantitative score (0-4) of the immunostaining for CD68 (macrophages), CD3 (T cells), CD20 (B cells) and CD138 (plasma cells). Patients were classified as: pauci-immune if CD68sublining (SL)<2 and/or CD3-CD20-CD138<1; diffuse-myeloid if CD68SL≥2, CD20<2 or CD138<2; lymphoid-myeloid if CD20≥2 or CD138>2. RNA sequencing of the ST was performed on 93RA/15PsA patients. Results: 39/183 patients were diagnosed with PsA (32 polyarticular, 7 oligoarticular) and 144/183 with RA (2010 ACR/EULAR criteria). Age was significantly lower in PsA patients. The comparison of the age-adjusted baseline variables showed: significantly higher number of tender and swollen joints in RA, but no significant differences between ESR, CRP and DAS28; higher US synovial thickening score of the biopsied joint in PsA, but comparable power-doppler. ST was obtained from small joints in 74.4% of PsA and 82% of RA. Histological comparison is summarised in Table 1 and 2. Only in RA, the pauci-immune pathotype associated with significantly lower ESR, CRP and DAS28 compared to lymphoid-myeloid; this association was maintained in a subset of 26 RA patients age- and gender-matched with the PsA population. Transcriptomic profiling showed that PsA-ST has significantly higher expression of the skin fibroblasts, eosinophils and neutrophils cellular gene modules. Genes significantly up regulated in PsA clustered in neutrophil recruitment/enrichment, cell migration and cytoskeleton remodelling modules. Conclusion: The identification of specific histological and molecular signatures characterising early-untreated PsA will help to better understand the disease pathogenesis and explore novel therapeutic targets. Reference: [1] van Kuijk AW, Tak PP. Synovitis in psoriatic arthritis: immunohistochemistry, comparisons with rheumatoid arthritis, and effects of therapy. Curr Rheumatol Rep. 2011 Aug;13(4):353-9    Disclosure of Interests: Alessandra Nerviani: None declared, Gloria Lliso Ribera: None declared, Marie Astrid Boutet: None declared, Katriona Goldmann: None declared, Stephen Kelly: None declared, Michele Bombardieri Grant/research support from: Celgene, Consultant for: Medimmune, Myles Lewis Grant/research support from: Celgene, Frances Humby: None declared, Costantino Pitzalis Grant/research support from: Celgene